Assessment of the Levels of Hopelessness among the Patients with Major Depressive Disorder in Sulaimani City - Taha Ahmad Faraj; Salwa Shakir Muhsin (Hawler Medical University, 2020)
Background and Objectives: Major depressive disorder associated with greater morbidity and mortality. Many researchers have sought complex association between depressions with hopelessness. The level of severity of such factors can play role in the causes, recovery and prediction of depression. The main objective of this study is to assess the levels of hopelessness among patients with major depressive disorder. Methods: A quantitative descriptive study design was conducted at a psychiatric clinic in the Ali Kamal Medical Consultation Center in Sulaimaniya City. A non-probability, convenient sampling was recruited of 150 patients with major depressive disorder attending the psychiatric clinic. The data was collected from December, 21st, 2017 to April 1st, 2018 by the researcher of current study through the utilization of structured interview guided by the questionnaire. Result: The results show that the patients with major depressive disorder experience moderate level to severe level of hopelessness. Suicidal attempt is a highly significant fac-tor affecting the levels of hopelessness. Conclusions: The study concluded that hopelessness value on its own the strongest significant factor may represent emotional source and possibly used to handle or cope with depressed mood by the patients.